Building an Organizational Culture that Supports Diversity and Inclusion - Anggoro, Agung; Anjarini, Ary Dwi (Penelitian dan Pengembangan Ilmu, 2024)
Building an organizational culture that supports diversity and inclusion is a significant challenge for organizations in this era of globalization. Through this research, we analyze the factors that influence the effectiveness of diversity and inclusion initiatives in organizations. The research results show that leadership commitment, inclusive policies, employee cultural awareness, employee involvement, and innovation play an important role in creating an inclusive and supportive work environment. Measuring the effectiveness of diversity and inclusion initiatives was also identified as an important step to ensure successful implementation. The practical and theoretical implications of these findings are discussed in the context of building an inclusive and supportive organizational culture.